Effectiveness of preventive cognitive therapy while tapering antidepressants versus maintenance antidepressant treatment versus their combination in prevention of depressive relapse or recurrence (DRD study): a three-group, multicentre, randomised controlled trial. (May 2018) - Bockting, Claudi L H; Klein, Nicola S; Elgersma, Hermien J; van Rijsbergen, Gerard D; Slofstra, Christien; Ormel, Johan; Buskens, Erik; Dekker, Jack; de Jong, Peter J; Nolen, Willem A; Schene, Aart H; Hollon, Steven D; et al.
Summary: Background: Keeping individuals on antidepressants after remission or recovery of major depressive disorder is a common strategy to prevent relapse or recurrence. Preventive cognitive therapy (PCT) has been proposed as an alternative to maintenance antidepressant treatment, but whether its addition would allow tapering of antidepressants or enhance the efficacy of maintenance antidepressant treatment is unclear. We aimed to compare the effectiveness of antidepressants alone, with PCT while tapering off antidepressants, or PCT added to antidepressants in the prevention of relapse and recurrence. Methods: In this single-blind, multicentre, parallel, three-group, randomised controlled trial, individuals recruited by general practitioners, pharmacists, secondary mental health care, or media were randomly assigned (10:10:8) to PCT and antidepressants, antidepressants alone, or PCT with tapering of antidepressants, using computer-generated randomised allocation stratified for number of previous depressive episodes and type of care. Eligible participants had previously experienced at least two depressive episodes and were in remission or recovery on antidepressants, which they had been receiving for at least the past 6 months. Exclusion criteria were current mania or hypomania, a history of bipolar disorder, any history of psychosis, current alcohol or drug abuse, an anxiety disorder that requires treatment, psychological treatment more than twice a month, and a diagnosis of organic brain damage. The primary outcome was time-related proportion of individuals with depressive relapse or recurrence in the intention-to-treat population, assessed four times in 24 months. Assessors were masked to treatment allocation, whereas physicians and participants could not be masked. This trial is registered with the Netherlands Trial Register, number NTR1907. Findings: Between July 14, 2009, and April 30, 2015, 2486 participants were assessed for eligibility and 289 were randomly assigned to PCT and antidepressant (n=104), antidepressant alone (n=100), or PCT with tapering of antidepressant (n=85). The overall log-rank test was significant (p=0·014). Antidepressants alone were not superior to PCT while tapering off antidepressants in terms of the risk of relapse or recurrence (hazard ratio [HR] 0·86, 95% CI 0·56–1·32; p=0·502). Adding PCT to antidepressant treatment resulted in a 41% relative risk reduction compared with antidepressants alone (0·59, 0·38–0·94; p=0·026). There were two suicide attempts (one in the antidepressants alone group and one in the PCT with tapering of antidepressants group) and one death (in the PCT and antidepressants group) not related to the interventions during the 24 months' follow-up. Interpretation: Maintenance antidepressant treatment is not superior to PCT after recovery, whereas adding PCT to antidepressant treatment after recovery is superior to antidepressants alone. PCT should be offered to recurrently depressed individuals on antidepressants and to individuals who wish to stop antidepressants after recovery. Funding: The Netherlands Organisation for Health Research and Development.